Valuing Life as an Asset, as a Statistic and at Gunpoint. Issue 643 (17th September 2021) - Hugonnier, Julien; Pelgrin, Florian; St-Amour, Pascal
Abstract: Rationalising the stark differences between the human capital and the statistical values of a human life is complicated by the absence of common foundations. We solve a human capital investment model with longevity risk to characterise the human capital. The associated indirect utility yields the willingness to pay against mortality; the marginal willingness to pay solves the value of a statistical life. Indifference between life and certain death characterises the limiting willingness to pay and provides a gunpoint value. A structural estimation reveals similar human capital (${\$}$ 300, 000) and gunpoint value (${\$}$ 251, 000) and explains a much larger statistical value (${\$}$ 4.98 million) by a strongly concave willingness to pay.